Some methodological and epistemological inconsistencies that can be incurred when the «leap» from data to abstract and analytical discourse, in Social Anthropology. Some critical notes - Hernández Lefranc, Harold (2022)
How the “leap” of the data, to the abstract discourse of interpretation and analysis, occurs in Social Anthropology, is a perennialepistemological and methodological question in the social sciences. The multivocality and historicity of the response, always plural,shows that the social sciences are also subject to the accidents of becoming, intersubjectivity, criticism, and historical processes,which affect the legitimacy of discourse. Notwithstanding this, and since extreme relativism is unacceptable, it can be acceptedthat there are certain methodological and epistemological problems that can be recognized, and that deserve to be overcome, inorder to avoid incurring in epistemological inconsistencies. Thus, what this text develops, as a pertinent exercise, is to point outand elucidate some of those let’s call them epistemological-methodological problems, which continuously occur as obstacles inthe researches of Social Anthropology, but which extend to all the particular disciplines of the Social Sciences.